Self-determination theory as a possible explanation for the motivation of Norwegian outdoor life students - Arne Martin Jakobsen (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2023)
Introduction: This study, based on the self-determination theory (SDT) by Deci and Ryan (1985), investigates the motivation among outdoor life students at universities and colleges in Norway. It also examines how students score on basic psychological needs, such as autonomy, competence, and relatedness, and their frequency of engagement in outdoor activities. The significance of the nature experience and the activity itself for the outdoor life students were analyzed, along with the extent to which the SDT can explain these two variables. Material and methods: The participants completed two standardized questionnaires. Results: The results showed a high degree of internal motivation and the most autonomous forms of external motivation, in addition to a high score on basic psychological needs. The students state that both nature experience and activity are important to them, with the former being the most important. Conclusions: The most active students in outdoor activities state that competence is an important basic psychological need. The importance of natural experience is mainly explained by a high score on self-determination as a psychological need, in addition to a high score on the most autonomous external motive: integrated regulation. Internal motivation is the main explanation for the importance of the activity for students.